2021
DOI: 10.3389/fnut.2020.606776
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Lemon Peel Polyphenols on Oxidative Stress-Induced Damage to Human Keratinocyte HaCaT Cells Through Activation of the Nrf2/HO-1 Signaling Pathway

Abstract: Lemon peel can be used as traditional Chinese medicine. Flavonoids are the most important components in lemon peel, which can be developed as natural medicine without side effects. This study investigated the protective effect of lemon peel polyphenols (LPP) on human keratinocyte HaCaT cells under oxidative stress. The active components of LPP were determined by high performance liquid chromatography. The abilities of LPP to scavenge DPPH and ABTS+ free radicals were studied for detection of antioxidation in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…The cytotoxicity effect of extracted PAs on Caco-2 cells were tested following Gao et al [ 34 ] with some modification. In addition, 100 μL of Caco-2 cells was seeded into 96-well plates at a density of 2 × 10 5 cells/well and incubated for 48 h in standard cell culture condition before being replaced by fresh medium.…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxicity effect of extracted PAs on Caco-2 cells were tested following Gao et al [ 34 ] with some modification. In addition, 100 μL of Caco-2 cells was seeded into 96-well plates at a density of 2 × 10 5 cells/well and incubated for 48 h in standard cell culture condition before being replaced by fresh medium.…”
Section: Methodsmentioning
confidence: 99%
“…A few studies have shown that HO-1 expression exerts immunomodulatory effects against inflammatory skin diseases, such as AD [ 22 , 23 ]. Nrf2, a transcription factor, binds to Keap1 in the cytoplasm, and when activated, Nrf2 separates from Keap1 and translocates to the nucleus, combines with antioxidant response element (ARE) to upregulate the expression of antioxidant enzymes, including HO-1, and induces cell protection [ 25 , 26 ]. Our results showed that compound 1 could significantly induce the expression of HO-1, while the translocation of Nrf2 from the cytosol to the nucleus was also promoted by alternate C ( 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, marine macro-and micro-algae seaweeds possess anti-metastatic and induce apoptosis of cancers in general [81]. Fruits are a rich source of great antioxidants and contain high polyphenols contents, which help reduce cancer risk [69][70][71][72][73]. Meanwhile, cruciferous vegetables such as cauliflower, broccoli, and brussels sprouts are a rich source of isothiocyanates.…”
Section: Natural Productsmentioning
confidence: 99%